Peran Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DP3A) Dalam Perlindungan Anak di Kota Makassar - Annisa Anderila Alwadina (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
The Indonesian Child Protection Commission (KPAI) recorded 2,355 cases of violations of children's rights and child protection reported up to August 2023. Article 21 of the Child Protection Law stipulates that local governments are obligated and responsible for respecting, protecting, and fulfilling children's rights without discrimination based on ethnicity, religion, race, social group, gender, culture, language, legal status, birth order, or physical and/or mental condition. The Office of Women's Empowerment and Child Protection (DP3A) is a regional technical agency responsible for carrying out local government affairs in the fields of women's empowerment and child protection in accordance with regional visions and missions. Although DP3A has made various efforts to prevent and address cases involving children, particularly cases of violence, the incidence of violence against children remains relatively high and has not shown a significant decline. This study aims to analyze the role of DP3A in the operational planning, implementation, control, and evaluation of child protection activities in Makassar City. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, documentation, and literature review and were analyzed using qualitative data analysis techniques. The results of the study indicate that the operational planning and implementation of child protection activities carried out by DP3A Makassar City are based on a responsive and inclusive Medium-Term Strategy. Furthermore, the control and evaluation mechanisms implemented by DP3A include case review meetings, community satisfaction surveys, performance and service quality evaluations, as well as the provision of technical guidance and training. These efforts demonstrate DP3A's commitment to strengthening child protection services and ensuring the fulfillment of children's rights in Makassar City.